Constitutions in the global financial crisis : a comparative analysis - Kontiadēs, Xenophōn I. (Ashgate, 2013)
The book includes contributions from prominent experts on Greece, Hungary, Iceland, Ireland, Italy, Latvia, Portugal, Spain, the UK, and the USA providing a critical analysis of the effects of the financial crisis on the constitution. The volume's extensive comparative chapter pins down distinct constitutional reactions towards the financial crisis, building an explanatory theory that accounts for the different ways constitutions responded to the crisis. How and why constitutions formed their reactions in the face of the financial crisis unravels throughout the book.